Pengembangan Modul Berbasis Survey, Question, Read, Reflect, Recite, Review (SQ4R) Pada Pembelajaran IPA - Anna Mardhia; Diyyan Marneli; M Haviz; Najmiatul Fajar (Edusainstika: Jurnal Pembelajaran MIPA, 2022)
This research is motivated by the fact found in the field that the low optimization of the use of teaching materials used by students, which causes the low mastery of science learning materials at MTsN 1 Tanah Datar. The teaching materials used are in the form of textbooks as a guide for teachers in the learning process. The weakness of the material described is incomplete, the images presented are not clear, have unattractive colors and are less creative in learning and students are less affective in learning. In the end, students cannot develop skills independently, which will affect student learning outcomes. To address this problem, the purpose of this research is to produce teaching materials in the form of Modules Based on Survey, Question, Read, Reflect, Recite, Review (SQ4R) on valid and practical science learning. The type of research applied through this activity is Research And Development using a 4-D model consisting of the Define, Design, Develop and Disseminate stages. The results showed that the module based on Survey, Question, Read, Reflect, Recite, Review (SQ4R) was obtained, namely, the resulting module was very valid with a validity value of 85.3% and an average practicality with 90% results based on teacher questionnaire responses and 90% based on student questionnaire responses in the very practical category, so that the Survey, Question, Read, Reflect, Recite, Review (SQ4R) based module can be used.